Biallelic loss of EMC10 leads to mild to severe intellectual disability. Issue 7 (9th June 2022) - Kaiyrzhanov, Rauan; Rocca, Clarissa; Suri, Mohnish; Gulieva, Sughra; Zaki, Maha S.; Henig, Noa Z.; Siquier, Karine; Guliyeva, Ulviyya; Mounir, Samir M.; Marom, Daphna; Allahverdiyeva, Aynur; Megahed, Hisham; et al.
Abstract: The endoplasmic reticulum membrane protein complex subunit 10 (EMC10) is a highly conserved protein responsible for the post‐translational insertion of tail‐anchored membrane proteins into the endoplasmic reticulum in a defined topology. Two biallelic variants in EMC10 have previously been associated with a neurodevelopmental disorder. Utilizing exome sequencing and international data sharing we have identified 10 affected individuals from six independent families with five new biallelic loss‐of‐function and one previously reported recurrent EMC10 variants. This report expands the molecular and clinical spectrum of EMC10 deficiency, provides a comprehensive dysmorphological assessment and highlights an overlap between the clinical features of EMC10 ‐and EMC1 ‐related disease.